Developing an Interactive Instructional Compact Disk for the Course of Basic Housekeeping - Nurlaila Nurlaila; Rusilanti Rusilanti (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
This research aimed at creating the product based on the concept of learning for basic housekeeping.  The development of interactive media in the form of interactive compact disk (CD) was conducted at Universitas Negeri Jakarta. Based on the review from the media expert, the total average score was categorized good i.e. 4,31. Meanwhile, from the material expert, the average score was categorized good i.e. 4,51 with the percentage of 90,28% and categorized as very good. The individual test (one to one) and the limited test showed the average scores of 4,13 and 4,09 respectively which were both categorized as good. In the field study, it was tested to 23 college students mutually and the total of average score was very good, i.e. 3,8 with the percentage score of 76 %. It showed that the quality of interactive CD of housekeeping course was very good.